Method for evaluating the electrical conductivity of different crystalline regions of a semi-crystalline cable insulation material by molecular simulation
Patent Information
- Application Number
- CN202611256591.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本发明的目的在于提供一种半结晶电缆绝缘材料不同晶区结构导电特性的分子模拟评估方法,以解决现有方法仅依靠静态空穴参数或单一离子迁移参数,无法对静态自由体积分数相近而界面链段运动不同的晶区结构进行有效区分的问题,实现由材料晶体结构输入到不同晶区结构相对离子输运趋势及离子导电促进或抑制作用的输出
[0053]与现有技术相比,本发明将局部密度、主链取向、RMSD、CED、FFV、链段MSD、空穴连通性及离子驻留、扩散和定向迁移等参量纳入统一分区与匹配条件框架,构建结构约束、界面动态可达性和离子输运特征参量体系,实现不同晶区结构相对离子输运趋势的分层评价,并从分子层面解释宏观导电变化趋势。该方法可区分静态自由体积相近但界面动力学不同的输运环境,减少重复制样与电学试验,降低研发成本。
Smart Images

Figure CN122907202A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of performance evaluation and molecular simulation technology of cable insulation materials, specifically relating to a molecular simulation evaluation method for the conductivity characteristics of semi-crystalline cable insulation materials with different crystalline regions. Background Technology
[0002] Semi-crystalline polymers possess crystalline, amorphous, and interfacial regions between these regions, exhibiting characteristics such as melt reprocessing, tunable mechanical properties, and good insulation performance, making them an important candidate system for recyclable cable insulation materials. Charge carriers need to migrate in a heterogeneous environment composed of crystalline lamellae, amorphous phases, and finite-thickness interfacial regions. Crystalline structure, chain conformation, molecular packing, interfacial chain segment movement, and hole connectivity can all influence their transport properties.
[0003] Existing studies typically use one or a few parameters, such as crystallinity, free volume fraction, mean square displacement, or ion migration trajectory, to explain the transport behavior of semi-crystalline insulating materials. Crystallinity only characterizes the crystal content and cannot reflect the constraint of different crystalline regions on adjacent interface segments; static free volume fraction can characterize the instantaneous void content but cannot explain whether holes can remain open and reconnect with adjacent holes over the ion movement timescale; a single ion trajectory is easily affected by initial position and local configuration; and the diffusion coefficient obtained by fitting a single time window may also be affected by local confined motion and the selection of the fitting interval. Therefore, relying solely on the above single parameters makes it difficult to provide a stable and interpretable evaluation of relative ion transport for insulating materials with similar total crystallinity but different crystalline regional structures.
[0004] Existing experimental results show that, even with essentially the same crystallinity, different crystal forms of polybutene-1 can still exhibit significantly different DC current densities and non-ohmic conductivity transition thresholds. This indicates that the factors determining conductivity differences include not only total crystallinity but also crystal chain conformation, crystal packing, and interfacial dynamics. However, macroscopic current measurements cannot directly analyze how the crystal structure alters the dynamic accessibility of interfacial holes and further affects ion migration. Current molecular simulations also lack an evaluation method that encompasses model construction, spatial partitioning, characteristic parameter calculation, relative ion transport trend output, and further establishes a trend correlation with experimental conductivity responses. Summary of the Invention
[0005] The purpose of this invention is to provide a molecular simulation evaluation method for the conductivity characteristics of different crystal region structures in semi-crystalline cable insulation materials. This method addresses the problem that existing methods, which rely solely on static hole parameters or single ion migration parameters, cannot effectively distinguish between crystal region structures with similar static free volume fractions but different interfacial chain segment movements. The invention achieves the output of the relative ion transport trends and the promoting or inhibiting effects of different crystal region structures, based on the input of the material's crystal structure.
[0006] To achieve the above objectives, the technical solution provided by the present invention is as follows:
[0007] S1. Construct a model that includes crystalline regions, a crystalline-amorphous region interface layer, and amorphous regions, and verify the effectiveness of the model based on characteristic diffraction peaks;
[0008] S2. Energy minimization, pre-relaxation, annealing, cooling and ensemble equilibrium were performed on different crystal region structure models. Molecular dynamics simulations were carried out under different temperature and electric field conditions to obtain the equilibrium configuration and molecular motion trajectory of different crystal region structures.
[0009] S3. Divide the thin layer along the direction perpendicular to the crystalline-amorphous region interface, and define the interface structure and ion transport parameter equations;
[0010] S4. Calculate the characteristic parameters of the interface structure of the crystalline region, the interface region, and the amorphous region for the crystalline region-amorphous region interface structure of different crystal forms;
[0011] S5. Introduce representative positive or negative ions into different crystal region structural models after equilibrium, and calculate the ion transport characteristic parameters of the crystal region, interface region and amorphous region.
[0012] S6. Under the same temperature and electric field conditions, correlate the interface structure characteristic parameters of S4 with the ion transport characteristic parameters of S5 to analyze the relative ion transport trends of different crystal regions and their promoting or inhibiting effects on the ion conduction process.
[0013] Further, in step S1, the model of the crystalline region, the crystalline-amorphous region interface layer, and the amorphous region includes the crystalline region located at both ends of the periodic unit cell and the amorphous region located between the two crystalline regions; under periodic boundary conditions, two equivalent crystalline-amorphous region interfaces without vacuum surfaces are formed, and different crystalline region structure models adopt the same or comparable crystalline region ratio and interface area; the model validity verification includes comparing the simulated X-ray diffraction peak positions and crystal plane assignments with the characteristic diffraction peaks of the target crystalline region structure.
[0014] Further, in step S2, the molecular dynamics simulation employs three-dimensional periodic boundary conditions and a 2 fs integration time step. The cutoff radii for the Lanner-Jones interaction and short-range Coulomb interaction are both 1.0 nm, and the long-range electrostatic interaction is handled using the particle mesh Ewald method. During density equilibrium, a semi-isotropic Parinello-Rachman pressure coupling of 1 bar and 5.0 ps is used, while keeping the direction parallel to the interface fixed, allowing relaxation only in the z-direction. For each model, based on energy minimization, the amorphous layer is pre-relaxed at 303 K and annealed to 500 K, followed by step cooling at 500, 450, 400, 350, and 303 K. After ensemble equilibrium via NVT and NPT, the model is then subjected to temperature conditions of 303, 343, and 363 K and 0, 0.03, and The NVT system was simulated under an electrostatic field.
[0015] Furthermore, in step S2, the energy of the ion system model is first minimized, and then balanced for 0.5 ns and 1.0 ns under NVT and NPT conditions, respectively. Subsequently, it is simulated for 30 ns under the NVT ensemble. The thermostat, interaction cutoff distance, electrostatic treatment method and integration time step are the same as those for the non-ion system model.
[0016] Furthermore, in step S3, the interface structures and ion transport parameters include local mass density, main chain orientation, crystal stability, free volume fraction, effective unbonded cohesive energy density, chain segment mean square displacement, ion distribution, regional residence probability, ion self-diffusion coefficient, and ion mobility.
[0017] The local mass density of the interface structure is:
[0018]
[0019] In the formula, This represents the position of the k-th spatial thin layer. Let be the mass of the i-th atom. The cross-sectional area is parallel to the interface. The thickness is denoted as ; the crystalline and amorphous regions are determined based on the plateau regions in the density and main chain orientation distribution after equilibrium; the continuous transition region between two plateaus is defined as the interface region; the average value of the two interfaces in each periodic cell is calculated separately.
[0020] The main chain orientation of the interface structure is:
[0021]
[0022] In the formula, P2 approaching 1 indicates that the molecular chain is highly oriented along the chain axis, and approaching 0 indicates that the orientation of the chain population is close to disorder. It is the angle between the local molecular chain backbone vector and the direction perpendicular to the interface.
[0023] The crystal stability of the interface structure is:
[0024]
[0025] In the formula, N is the number of atoms in the crystal region. This represents the position of the atom in the aligned equilibrium reference configuration. This represents the position of the atom in the aligned equilibrium reference structure.
[0026] The free volume fraction of the interface structure is:
[0027]
[0028] In the formula, V is the total volume of the region being analyzed. The volume occupied by molecules.
[0029] The effective unbonded cohesive energy density of the interface structure is:
[0030]
[0031] In the formula, For van der Waals interaction energy, Let V be the electrostatic interaction energy, and V be the volume of the corresponding region. The negative sign in the formula makes a stronger net attraction correspond to a larger positive value.
[0032] The mean square displacement of the chain segments in the interface structure is:
[0033]
[0034] In the formula, and These represent the positions of main chain atom j at the initial time t0 and after a lag time t, respectively.
[0035] The ion distribution of the ion transport is as follows:
[0036]
[0037] In the formula, Let be the number of ion coordinates sampled in the k-th thin layer. Since each system contains only one probe ion, the normalized distribution represents the probability that the ion is located in the corresponding thin layer.
[0038] The regional residence probability of the ion transport is:
[0039]
[0040] In the formula, Let be the number of frames analyzed; when the ion in the j-th frame is located in region R, ,otherwise .
[0041] Under zero electric field, the ion self-diffusion coefficient of the ion transport is:
[0042]
[0043] Each model was fitted with the mean square displacement slope in three time intervals: 2–10, 5–20, and 10–28 ns. The median of the three estimates was denoted as D. mathrm Under zero electric field, D mathrm This is the mean square displacement estimate; however, under a finite electric field, D... mathrm It is the mean square displacement slope transport descriptor.
[0044] The ion transport ion migration rate is:
[0045]
[0046] Under a non-zero electric field, the mobility of the ion transport is:
[0047]
[0048] In the formula, The magnitude of the applied electric field is expressed in terms of charge alignment. and A positive value indicates that the ion moves along the direction of the electric field force it experiences. When = 0, the mobility is mathematically undefined.
[0049] Furthermore, in step S4, the interface characteristic parameters include parameters such as local mass density, chain orientation, cohesive energy density, free volume fraction, and mean square displacement of chain segments.
[0050] Furthermore, in step S5, the ion transport characteristic parameters include parameters such as ion distribution, residence time, self-diffusion coefficient, ion migration velocity, and mobility.
[0051] Furthermore, in step S6, the correlation evaluation is performed according to the order of interface structure constraint degree and ion directional migration capability; when a crystal region structure exhibits stronger structural constraint, lower mean square displacement of interface region chain segments, and lower charge alignment drift velocity, net displacement, and effective cross-region number, it is considered that the crystal region structure has weaker relative ion transport capability; when the change order of the interface region free volume fraction and dynamic parameters is inconsistent, the determination is made by combining the mean square displacement of interface region chain segments, hole connectivity, and ion directional transport parameters.
[0052] The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions, as described in this invention, has the following advantages:
[0053] Compared with existing technologies, this invention incorporates parameters such as local density, main chain orientation, RMSD, CED, FFV, segment MSD, hole connectivity, and ion residence, diffusion, and directional migration into a unified partitioning and matching condition framework. It constructs a parameter system for structural constraints, interface dynamic accessibility, and ion transport characteristics, enabling hierarchical evaluation of the relative ion transport trends of different crystal regions and explaining macroscopic conductivity changes at the molecular level. This method can distinguish transport environments with similar static free volumes but different interface dynamics, reducing the need for repeated sampling and electrical experiments, and lowering R&D costs. Attached Figure Description
[0054] Figure 1 This is a flowchart illustrating the overall simulation process of the present invention.
[0055] Figure 2 This is a comparison diagram of the simulated and experimental X-ray diffraction patterns of PB-1 Type I and Type II in this invention.
[0056] Figure 3 This is a model diagram of the PB-1 crystalline region-amorphous region-crystalline region of the present invention.
[0057] Figure 4 This is a representative ion-containing PB-1 crystalline-amorphous-crystalline region model diagram of the present invention. Detailed Implementation
[0058] The present invention will now be described in detail with reference to the accompanying drawings. In the description of the embodiments of the present invention, the terms "first" and "second" are used only to distinguish different objects and should not be construed as implying relative importance or limiting the number of technical features. Clearly, the described embodiments are only for explaining the present invention, and the accompanying drawings only show some, not all, aspects related to the present invention.
[0059] This invention provides a molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline region structures, such as... Figure 1 As shown, the method includes the following steps:
[0060] S1. Construct a model that includes crystalline regions, a crystalline-amorphous region interface layer, and amorphous regions. Verify the effectiveness of the model based on characteristic diffraction peaks.
[0061] The model of the crystalline region, the crystalline-amorphous region interface layer, and the amorphous region includes the crystalline region located at both ends of the periodic unit cell and the amorphous region located between the two crystalline regions; under periodic boundary conditions, two equivalent crystalline-amorphous region interfaces without vacuum surfaces are formed, and different crystalline region structure models adopt the same or comparable crystalline region ratio and interface area; the model validity verification includes comparing the simulated X-ray diffraction peak positions and crystal plane assignments with the characteristic diffraction peaks of the target crystalline region structure.
[0062] S2. Energy minimization, pre-relaxation, annealing, cooling, and ensemble equilibrium were performed on different crystal region structure models. Molecular dynamics simulations were conducted under different temperature and electric field conditions to obtain the equilibrium configurations and molecular trajectories of different crystal region structures.
[0063] Molecular dynamics simulations employed three-dimensional periodic boundary conditions and a 2 fs integration time step. The cutoff radii for Lanner-Jones interactions and short-range Coulomb interactions were both 1.0 nm, while long-range electrostatic interactions were handled using the particle mesh Ewald method. During density equilibrium, a semi-isotropic Parinello-Rachman pressure coupling of 1 bar and 5.0 ps was used, while maintaining a fixed direction parallel to the interface and allowing relaxation only in the z-direction. For each model, based on energy minimization, the amorphous layer was pre-relaxed at 303 K and annealed to 500 K, followed by sequential step cooling at 500, 450, 400, 350, and 303 K. After ensemble equilibrium via NVT and NPT, subsequent simulations were performed at 303, 343, and 363 K and 0.03 and 0.03 nm. The NVT system was simulated under an electrostatic field.
[0064] The energy of the ion system model was first minimized, and then balanced for 0.5 ns and 1.0 ns under NVT and NPT conditions, respectively. Subsequently, the model was simulated for 30 ns under the NVT ensemble. The thermostat, interaction cutoff distance, electrostatic treatment method, and integration time step were the same as those used in the simulation with only polymers.
[0065] S3. Divide the thin layer along the direction perpendicular to the crystalline-amorphous region interface, and then define the interface structure and ion transport parameter equations.
[0066] The interface structures and ion transport parameters mentioned include local mass density, main chain orientation, crystal stability, free volume fraction, effective unbonded cohesive energy density, chain segment mean square displacement, ion distribution, regional residence probability, ion self-diffusion coefficient, and ion mobility.
[0067] The local mass density of the interface structure is:
[0068]
[0069] In the formula, This represents the position of the k-th spatial thin layer. Let be the mass of the i-th atom. The cross-sectional area is parallel to the interface. The thickness is denoted as ; the crystalline and amorphous regions are determined based on the plateau regions in the density and main chain orientation distribution after equilibrium; the continuous transition region between two plateaus is defined as the interface region; the average value of the two interfaces in each periodic cell is calculated separately.
[0070] The main chain orientation of the interface structure is:
[0071]
[0072] In the formula, P2 approaching 1 indicates that the molecular chain is highly oriented along the chain axis, and approaching 0 indicates that the orientation of the chain population is close to disorder. It is the angle between the local molecular chain backbone vector and the direction perpendicular to the interface.
[0073] The crystal stability of the interface structure is:
[0074]
[0075] In the formula, N is the number of atoms in the crystal region. This represents the position of the atom in the aligned equilibrium reference configuration. This represents the position of the atom in the aligned equilibrium reference structure.
[0076] The free volume fraction of the interface structure is:
[0077]
[0078] In the formula, V is the total volume of the region being analyzed. The volume occupied by molecules.
[0079] A spherical probe with a radius of 0.05 nm was used to plot the probe's reachable free volume on a 3D mesh. The analysis included the overall and regional free volume fractions, the volume fraction of the largest connected void clusters, and connectivity in directions parallel and perpendicular to the interface. These descriptive quantities can distinguish between the total amount of voids and the formation of potential walkable paths.
[0080] The effective unbonded cohesive energy density of the interface structure is:
[0081]
[0082] In the formula, For van der Waals interaction energy, Let V be the electrostatic interaction energy, and V be the volume of the corresponding region. The negative sign in the formula makes a stronger net attraction correspond to a larger positive value.
[0083] The mean square displacement of the chain segments in the interface structure is:
[0084]
[0085] In the formula, and These represent the positions of main chain atom j at the initial time t0 and after a lag time t, respectively.
[0086] The ion distribution of the ion transport is as follows:
[0087]
[0088] In the formula, Let be the number of ion coordinates sampled in the k-th thin layer. Since each system contains only one probe ion, the normalized distribution represents the probability that the ion is located in the corresponding thin layer.
[0089] The regional residence probability of the ion transport is:
[0090]
[0091] In the formula, Let be the number of frames analyzed; when the ion in the j-th frame is located in region R, ,otherwise .
[0092] Under zero electric field, the ion self-diffusion coefficient of the ion transport is:
[0093]
[0094] Each model was fitted with the mean square displacement slope in three time intervals: 2–10, 5–20, and 10–28 ns. The median of the three estimates was denoted as D. mathrm Under zero electric field, D mathrm This is the mean square displacement estimate; however, under a finite electric field, D... mathrm It is the mean square displacement slope transport descriptor.
[0095] The ion transport ion migration rate is:
[0096]
[0097] Under a non-zero electric field, the mobility of the ion transport is:
[0098]
[0099] In the formula, The magnitude of the applied electric field is expressed in terms of charge alignment. and A positive value indicates that the ion moves along the direction of the electric field force it experiences. When = 0, the mobility is mathematically undefined.
[0100] S4. Calculate the characteristic parameters of the interface structure of the crystalline region, the interface region, and the amorphous region for different crystal forms.
[0101] Interface characteristic parameters include local mass density, chain orientation, cohesive energy density, free volume fraction, and mean square displacement of chain segments.
[0102] S5. Introduce representative positive or negative ions into the equilibrium crystal region structure models respectively, and calculate the ion transport characteristic parameters of the crystalline region, interface region, and amorphous region.
[0103] Ion transport characteristic parameters include ion distribution, residence time, self-diffusion coefficient, ion migration velocity, and mobility.
[0104] S6. Under the same temperature and electric field conditions, correlate the interface structure characteristic parameters of S4 with the ion transport characteristic parameters of S5 to analyze the relative ion transport trends of different crystal regions and their promoting or inhibiting effects on ion conduction processes.
[0105] The evaluation is based on the degree of interface structural constraint and the ion directional migration capability. When a crystal region structure exhibits stronger structural constraint, lower mean square displacement of the interface region chain segments, and lower charge alignment drift velocity, net displacement, and effective cross-region number, it is considered to have a weaker relative ion transport capability. When the order of change of the interface region free volume fraction and dynamic parameters is inconsistent, the determination is made by combining the mean square displacement of the interface region chain segments, hole connectivity, and ion directional transport parameters.
[0106] The following is a specific embodiment: In this embodiment, the first and second crystal forms of polybutene-1 are selected as the verification objects. Polybutene-1 is only used as a verification material for the method of the present invention and does not constitute a limitation on the types of materials applicable to the present invention, as detailed below:
[0107] 1. Model Building
[0108] Different crystal region structures include type I and type II crystals of polybutene-1. Type I molecular chains adopt a 3 / 1 helical conformation, while type II molecular chains adopt an 11 / 3 helical conformation. The molecular chain axes of both models are arranged along the z-direction of the model, and the crystallographic unit cell is periodically replicated to form a crystal supercell.
[0109] The crystal model was validated by comparing the simulated X-ray diffraction patterns with the experimental patterns of PB-1 Type I and Type II. The Type I simulation reproduced approximately... and The characteristic peaks at (110) and (300) and the characteristic peaks at (220) and (211) between 20 and 21 were reproduced by the Type II simulation. , and The simulated peaks at (200), (220), and (213) are characteristic peaks. The simulated peak positions and crystal plane assignments correspond to the target crystal form, indicating that the established model can reflect the crystal structure characteristics of type I and type II. The comparison between the simulated and experimental X-ray diffraction patterns of PB-1 type I and type II is as follows: Figure 2 As shown.
[0110] The validated supercell was extended laterally and transformed into a C / A / C model. Two crystalline layers were placed at the upper and lower boundaries along the z-direction, respectively, with an amorphous PB-1 layer in between. Under periodic boundary conditions, this resulted in two equivalent crystalline-amorphous region interfaces without vacuum surfaces. The experimentally measured crystallinity of type I and type II was 48.9% and 48.8%, respectively. Therefore, the two models adopted comparable phase region proportions: 45% crystalline region, 10% initial transition region, and 45% amorphous core region along the z-direction. The initial type I and type II systems contained 7008 and 6400 atoms, respectively, and had similar interface areas. By changing the amorphous chain arrangement and initial velocity, three independent configurations were generated for each crystal form. The PB-1 crystalline-amorphous-crystalline region model is shown below. Figure 3 As shown.
[0111] After equilibrium, the C / A / C model was evaluated using spatial density distribution, main chain orientation, RMSD, free volume, effective unbonded cohesion, and mean square displacement of chain segments. The equilibrium density distribution remained continuous between the crystalline and amorphous regions, while the crystalline layers maintained their characteristic 3 / 1 and 11 / 3 helical structures. The interface region was determined based on the range of continuous transition from the plateau value in the crystalline region to the plateau value in the amorphous region, determined by density and orientation. The two interfaces in each periodic cell were analyzed separately and averaged. The repeatability of the results was evaluated using three independent models under 303 K and zero electric field conditions.
[0112] 2. Molecular dynamics simulation
[0113] Both models employ three-dimensional periodic boundary conditions, a GAFF2 force field, an integration time step of 2 fs, a cutoff distance of 1.0 nm for Lanner-Jones interactions and short-range Coulomb interactions, and a particle mesh Ewald method for long-range electrostatic interactions. Hydrogen bonds are constrained using the LINCS algorithm. Temperature is controlled by a velocity rescaling thermostat with a coupling time of 1.0 ps; pressure is controlled by a semi-isotropic Parinello-Rachman method with a coupling time of 1 bar and a coupling time of 5.0 ps. Lateral dimensions parallel to the interface are kept fixed, allowing only relaxation in the z-direction. Each model first undergoes energy minimization, followed by pre-relaxation of the amorphous layer at 303 K under constrained crystalline conditions, followed by annealing to 500 K. Subsequently, the model undergoes step cooling at 500 K, 450 K, 400 K, 350 K, and 303 K, while gradually releasing the constraints.
[0114] The cooled model was first equilibrated in an NVT ensemble at 303 K, and then in a semi-isotropic NPT ensemble at 303 K and 1 bar. After the cell size, density, temperature, and potential energy stabilized, simulations were performed in the NVT ensemble.
[0115] Three independent configurations for each crystal form were used for zero-field simulations at 303, 343, and 363 K. Non-zero-field states evolved from a representative equilibrium model for each crystal form, with each polymer-only production trajectory having a length of 10 ns. Therefore, zero-field results are expressed as mean ± sample standard deviation, while 0.03 and... The state is used for matching comparisons and trend analysis between crystal forms.
[0116] 3. Analysis of the crystalline-amorphous region interface structure and dynamics
[0117] The model was divided into spatial thin layers along the z-axis, and the same thin-layer definition, sampling interval, and trajectory time window were used to calculate the local mass density and main chain orientation parameters. The stable region inside the crystalline layer was defined as the crystalline region, the stable region in the middle of the amorphous layer was defined as the amorphous region, and the region where the density and orientation continuously changed between the two regions was defined as the crystalline-amorphous region interface region. The two interfaces in the periodic unit cell were calculated separately and then averaged. Both models maintained a continuous crystalline-amorphous-crystalline region structure after equilibrium, with the crystalline layers maintaining 3 / 1 and 11 / 3 helical structures, respectively. The main structural and interface characteristic parameters obtained under 303 K and zero electric field conditions are shown in Table 1.
[0118] The overall densities of types I and II are respectively and The partition group densities used for comparison are as follows: crystal region and Interface area and amorphous region and Therefore, the denser packing of Type I extends from the crystalline region to the transition region and the intermediate amorphous layer. Furthermore, increasing the temperature reduces the density of both crystal forms at zero electric field, but the relaxation is more pronounced in Type II. The density of Type I decreases from that at 303 K. When it drops to 343 K And 363 K Type II is composed of Continue to decline and Therefore, when the K increases from 303 K to 363 K, the total density decreases for Type I and Type II are respectively... and .
[0119] The density difference is accompanied by a significant difference in chain orientation. At 303 K and under zero electric field, the P2 of the type I crystal region is 0.3699 ± 0.0014, and that of the type II is 0.2551 ± 0.0081. The type I interface region maintains a positive orientation, with a P2 of 0.1071 ± 0.0146; the type II interface region is close to a disordered reference state, with a P2 of 0.0205 ± 0.0190. The amorphous regions of both crystal types are essentially unoriented. The P2 of the type I crystal region hardly changes with temperature, being 0.3699, 0.3709, and 0.3684 at 303, 343, and 363 K, respectively; while that of the type II increases from 0.2551 to 0.2769 and 0.2836, but remains lower than that of the type I at all temperatures. After applying an electric field, both crystal types maintain the same density relationship, and the type I maintains a positive interface orientation under all conditions.
[0120] Table 1. Main structural and interface characteristic parameters of different crystal regions
[0121]
[0122] The RMSD of crystalline regions provides an independent evaluation index for structural stability. The RMSD of type I is 0.0646±0.0019 nm, which is 62% lower than that of type II (0.1719±0.0227 nm). In contrast, the RMSDs of the amorphous regions of the two crystalline types are 0.2627±0.0490 nm and 0.2407±0.0456 nm, respectively, overlapping within the discrete range. Therefore, the significant RMSD difference is mainly confined to the crystal framework. Throughout the temperature-electric field matrix, the P2 difference between type I and type II crystalline regions remains positive, indicating that type I maintains its orientation advantage under thermal and electrical perturbations.
[0123] The denser Type I structure also corresponds to a higher effective unbonded cohesive energy density. At 303 K and under zero electric field conditions, the cohesive energy densities of Type I and Type II are respectively... and Heating reduces the cohesive energy density of both systems. The above analysis shows that Type I exhibits higher overall density, crystalline region density, chain orientation parameters, lower crystalline region RMSD, and higher effective unbonded cohesive energy density, indicating that Type I crystals are more densely packed and have stronger structural constraint on crystalline regions and adjacent interface chain segments.
[0124] Notably, the representative configuration at 303 K and zero electric field shows that the probe's reachable free volume is mainly concentrated in the amorphous region and its adjacent interface region. Type II also exhibits more extensive porosity infiltration into the crystalline region, while Type I has fewer and more isolated porosities in the crystalline region. Since each image corresponds to only one instantaneous configuration, the quantitative interpretation is based on trajectory statistics. At 303 K and zero electric field, the overall free volume fractions for Type I and Type II are 0.0745±0.0034 and 0.0827±0.0065, respectively. The partitioning results indicate that the crystalline region is the main source of the difference in free volume between the two crystal forms: the free volume fractions for Type I and Type II crystalline regions are 0.0305 and 0.0693, respectively. In contrast, the free volume fractions in the interface region are almost identical for both crystal forms, at 0.1269 and 0.1261, respectively; the values for the amorphous region are also similar, at 0.0922 and 0.0874, respectively. Therefore, Type I mainly reduces the free volume in the crystalline region, rather than uniformly reducing the free volume throughout the entire unit cell.
[0125] The crystal form-dependent kinematic differences are most significant in the crystalline and interface regions. At 303 K and under zero electric field conditions, the mean square displacements of the type I and type II crystalline regions within the 4–5 ns time interval are respectively... and The corresponding values in the interface area are respectively and That is, Type I is reduced by approximately 78% and Type II, respectively. The values for the amorphous regions of the two crystalline forms are more similar, respectively. and Furthermore, the dispersion is greater. This indicates that similar static free volume fractions can correspond to different dynamic accessibility at the interface. The above results show that the comparison between the free volume fraction and the mean square displacement of the interface region reveals why static free volume alone cannot distinguish between the two transport environments. Although the free volume fractions of the interface region are almost the same for both crystal forms at 303 K, the mean square displacement of the interface region of type II is more than three times that of type I. When the relaxation rates of the surrounding chains are different, similar instantaneous void fractions may have drastically different dynamic accessibility. This separation between static hole content and dynamic opening capability is consistent with the conclusions of existing simulation and probe diffusion studies, namely that transport depends simultaneously on void structure and chain segment relaxation.
[0126] Overall, the Type I lattice with a 3 / 1 helical structure forms denser and more oriented crystalline regions with lower free volumes and significantly weaker interface mobility. The defining characteristic of Type I is not that the free volume decreases uniformly across all regions, but rather that the dense crystal is coupled with an interface region where transient vacancies are difficult to open and reconnect.
[0127] 4. Representative ion transport analysis
[0128] In ion transport simulations, a Na+ ion is introduced into the equilibrium C / A / C model. + Or a Cl - Its initial position is located in an accessible amorphous region and does not overlap with other atoms, such as Figure 4 As shown. The Lanner-Jones ion parameters were obtained using the Joung-Cheatham monovalent ion parameter set, and the single-ion PME calculations were performed against a uniform neutralized background. Each ion-containing system was first subjected to energy minimization, and then equilibrated for 0.5 ns and 1.0 ns under NVT and semi-isotropic NPT conditions, respectively, followed by simulation for 30 ns in the NVT ensemble.
[0129] Ion distribution, regional residence, and cross-regional events are normalized using boundaries corresponding to structural partitions, crystalline regions, crystalline-amorphous interface regions, and amorphous regions. The boundary values are 0.24, 0.31, 0.69, and 0.76. A valid cross-region event is counted only when an ion enters a new structural region and remains continuously for at least 0.10 ns. In the combined statistics of the nine states, type II Na... + 84.60% of the sampling frames are located in the amorphous region; Type I Na + The occupancy rates of Na in the crystalline and amorphous regions were 48.74% and 47.61%, respectively. + The occupancy rates in the type I and type II interface regions were 3.65% and 1.56%, respectively, with median residence times of 0.23 and 0.26 ns, respectively. -The sampling of the interface region is more thorough, with occupancy rates of 28.32% and 18.85% in the type I and type II interface regions, respectively, and median dwell times of 1.18 and 0.95 ns, respectively. The above-mentioned merged occupancy rates are used to describe the localization situation in all states and are not used as equilibrium allocation coefficients.
[0130] Under zero electric field, the diffusion coefficient was calculated within time windows of 2–10 ns, 5–20 ns, and 10–28 ns, and the median of the results for each time window was taken as D. mathrm Under a finite electric field, the charge-aligned drift velocity is used. Charge alignment mobility Net displacement and effective number of crossings are used to evaluate the directional transport capacity of ions. Na + D at 303, 343, and 363K in Type I mathrm The values were 0.8679, 2.6944, and respectively. In type II, the values were 0.4181, 4.4184, and [other values]. The zero-field results above do not show a consistent crystal form order at all temperatures, indicating that the overall transport level of type I or type II cannot be determined solely based on the zero-field diffusion coefficient.
[0131] Directional transport under a finite electric field exhibits more pronounced crystal structure differences. Below, type II Na⁺ At 303, 343, and 363 K, the values are 2.236, 5.558, and [missing value], respectively. The values for type I were 0.927, 0.871, and... In 363K, Under these conditions, Na + Representative transport results are shown in Table 2.
[0132] Table 2. Directional transport results of Na+ in different crystal regions
[0133]
[0134] Under the above conditions, type II Na + A total of 51 valid region transfers satisfying the 0.10 ns persistence criterion occurred. - The absolute directional migration response is lower than that of Na⁺, but at 363 K, Below, in type I and type II They are 0.0231 and 0.0231 respectively. The signed net displacements were -1.34 nm and -11.02 nm, respectively, which also indicates that the directional migration response of type II is stronger than that of type I under high temperature and high electric field. After averaging over nine states, Na +Within every 30 ns, 18.0 and 20.3 effective region transfers occurred in type I and type II, respectively. - The numbers were 8.0 and 10.2 respectively.
[0135] The above results indicate that the Type I crystal region structure exerts stronger constraints on the interface chain segments, making it more difficult for transient holes to be continuously opened and reconnected, and the directional migration of representative ions is more significantly suppressed. The Type II interface region shows stronger chain segment movement, making it easier for holes to be dynamically opened and form transient channels for ion migration. It can be considered that the relative ion transport tendency of Type I is lower than that of Type II, and it exhibits a stronger inhibitory effect on ion conduction processes.
[0136] 5. Experimental Trend Verification
[0137] To verify the accuracy of the simulation, DC conductivity tests were conducted on type I and type II polybutene materials (iPB and PBA) at 303K with electric field strengths of 30kV / mm and 70kV / mm, respectively. These conditions correspond to the simulation settings. The test results are shown in Table 3.
[0138] Table 3. Comparison of experimental trends between Type I and Type II within the same material system.
[0139]
[0140] Experimental results show that, at the same temperature, Type I exhibits lower current density and higher threshold electric field compared to Type II, indicating that the Type I crystal structure can suppress carrier migration. The simulation results obtained in this embodiment, showing that "Type I has weaker chain segment motion in the interface region and a lower representative ion directional migration response, thus its relative ion transport tendency is lower than that of Type II," are consistent with the aforementioned experimental trends. For ion currents controlled by mobility within the ohmic region, at similar carrier concentrations, lower effective mobility corresponds to lower ion current contribution; stronger interface structure constraints also mean that forming continuous migration paths requires stronger thermal or electric field activation, which is consistent with the wider ohmic region and higher transition threshold of Type I.
[0141] It should be noted that this embodiment uses a single representative ion to compare the relative transport trends of different crystal regions. The actual carrier concentration in the experimental material was not set, nor were electron trapping, electrode injection, space charge confinement current, or high-field electron conduction processes explicitly simulated. Therefore, the experimental verification is a consistency verification of relative trends and molecular mechanisms; the simulated ion mobility is not directly converted to experimental absolute conductivity, nor are the simulation results numerically compared with experimental current densities.
[0142] The above is a demonstration of one embodiment of the present invention. Those skilled in the art can modify or equivalently replace the model size, force field type, ion type, temperature, electric field, sampling time, and continuous cross-region threshold without departing from the spirit and scope of the present invention. This method can also be applied to other semi-crystalline polymer cable insulation materials with crystalline regions, crystalline-amorphous region interface layers, and amorphous regions. All embodiments falling within the scope of the claims of this invention are protected by this invention.
Claims
1. A molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline region structures, characterized in that, The method includes the following steps: S1. Construct a model that includes crystalline regions, a crystalline-amorphous region interface layer, and amorphous regions, and verify the effectiveness of the model based on characteristic diffraction peaks; S2. Energy minimization, pre-relaxation, annealing, cooling and ensemble equilibrium were performed on different crystal region structure models. Molecular dynamics simulations were carried out under different temperature and electric field conditions to obtain the equilibrium configuration and molecular motion trajectory of different crystal region structures. S3. Divide the thin layer along the direction perpendicular to the crystalline-amorphous region interface, and define the interface structure and ion transport parameter equations; S4. Calculate the characteristic parameters of the interface structure of the crystalline region, the interface region, and the amorphous region for the crystalline region-amorphous region interface structure of different crystal forms; S5. Introduce representative positive or negative ions into different crystal region structural models after equilibrium, and calculate the ion transport characteristic parameters of the crystal region, interface region and amorphous region. S6. Under the same temperature and electric field conditions, correlate the interface structure characteristic parameters of S4 with the ion transport characteristic parameters of S5 to analyze the relative ion transport trends of different crystal regions and their promoting or inhibiting effects on the ion conduction process.
2. The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions according to claim 1, characterized in that: In step S1, the model of the crystalline region, the crystalline-amorphous region interface layer, and the amorphous region includes the crystalline region located at both ends of the periodic unit cell and the amorphous region located between the two crystalline regions; under periodic boundary conditions, two equivalent crystalline-amorphous region interfaces without vacuum surfaces are formed, and different crystalline region structure models use the same or comparable crystalline region ratio and interface area; the model validity verification includes comparing the simulated X-ray diffraction peak positions and crystal plane assignments with the characteristic diffraction peaks of the target crystalline region structure.
3. The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions according to claim 1, characterized in that: In step S2, the molecular dynamics simulation employs three-dimensional periodic boundary conditions and a 2 fs integration time step. The cutoff radii for the Lanner-Jones interaction and short-range Coulomb interaction are both 1.0 nm, and the long-range electrostatic interaction is handled using the particle mesh Ewald method. During the density equilibrium process, a semi-isotropic Parinello-Rachman pressure coupling of 1 bar and 5.0 ps is used, while keeping the direction parallel to the interface fixed and allowing relaxation only in the z-direction. For each model, based on energy minimization, the amorphous layer is pre-relaxed at 303 K and annealed to 500 K, followed by step cooling at 500, 450, 400, 350, and 303 K. After ensemble equilibration of NVT and NPT, subsequent tests were conducted at temperatures of 303, 343, and 363 K and at concentrations of 0, 0.03, and... The NVT system was simulated under an electrostatic field.
4. The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions according to claim 1, characterized in that: In step S2, the energy of the ion system model is first minimized, and then balanced for 0.5 ns and 1.0 ns under NVT and NPT conditions, respectively. Subsequently, it is simulated for 30 ns under the NVT ensemble. The thermostat, interaction cutoff distance, electrostatic treatment method and integration time step are the same as those for the non-ion system model.
5. The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions according to claim 1, characterized in that, In step S3, the interface structures and ion transport parameters include local mass density, main chain orientation, crystal stability, free volume fraction, effective unbonded cohesive energy density, chain segment mean square displacement, ion distribution, regional residence probability, ion self-diffusion coefficient, and ion mobility. The local mass density of the interface structure is: In the formula, This represents the position of the k-th spatial thin layer. Let be the mass of the i-th atom. The cross-sectional area is parallel to the interface. The thickness is given by the thin film thickness; the crystalline and amorphous regions are determined based on the plateau regions in the density and main chain orientation distribution after equilibrium; the continuous transition region between two plateaus is defined as the interface region; the two interfaces in each periodic unit cell are calculated separately and then averaged. The main chain orientation of the interface structure is: In the formula, P2 approaching 1 indicates that the molecular chain is highly oriented along the chain axis, and approaching 0 indicates that the orientation of the chain population is close to disorder. The angle between the local molecular chain backbone vector and the direction perpendicular to the interface; The crystal stability of the interface structure is: In the formula, N is the number of atoms in the crystal region. This represents the position of the atom in the aligned equilibrium reference configuration. This represents the position of the atom within the aligned equilibrium reference structure; The free volume fraction of the interface structure is: In the formula, V is the total volume of the region being analyzed. For the volume occupied by molecules; The effective unbonded cohesive energy density of the interface structure is: In the formula, For van der Waals interaction energy, Let V be the electrostatic interaction energy, and V be the volume of the corresponding region. The negative sign in the formula makes a stronger net attraction correspond to a larger positive value. The mean square displacement of the chain segments in the interface structure is: In the formula, and These represent the positions of main chain atom j at the initial time t0 and after a lag time t, respectively. The ion distribution of the ion transport is as follows: In the formula, Let be the number of ion coordinates sampled in the k-th thin layer. Since each system contains only one probe ion, the normalized distribution represents the probability that the ion is located in the corresponding thin layer. The regional residence probability of the ion transport is: In the formula, Let be the number of frames analyzed; when the ion in the j-th frame is located in region R, ,otherwise ; Under zero electric field, the ion self-diffusion coefficient of the ion transport is: Each model was fitted with the mean square displacement slope in three time intervals: 2–10, 5–20, and 10–28 ns. The median of the three estimates was denoted as D. mathrm Under zero electric field, D mathrm This is the mean square displacement estimate; however, under a finite electric field, D... mathrm The mean square displacement slope is the transport descriptor. The ion transport ion migration rate is: Under a non-zero electric field, the mobility of the ion transport is: In the formula, The magnitude of the applied electric field is expressed in terms of charge alignment. and A positive value indicates that the ion moves along the direction of the electric field force it experiences. When = 0, the mobility rate is mathematically undefined.
6. The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions according to claim 1, characterized in that: In step S4, the interface characteristic parameters include parameters such as local mass density, chain orientation, cohesive energy density, free volume fraction, and mean square displacement of chain segments.
7. The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions according to claim 1, characterized in that: In step S5, the ion transport characteristic parameters include parameters such as ion distribution, residence time, self-diffusion coefficient, ion migration velocity, and mobility.
8. The molecular simulation evaluation method for the conductivity properties of semi-crystalline cable insulation materials with different crystalline regions according to claim 1, characterized in that: In step S6, the correlation evaluation is performed in the order of interface structure constraint degree and ion directional migration capability. When a crystal region structure exhibits stronger structural constraint, lower mean square displacement of interface region chain segments, and lower charge alignment drift velocity, net displacement, and effective cross-region number, it is considered that the crystal region structure has weaker relative ion transport capability. When the change order of the interface region free volume fraction and dynamic parameters is inconsistent, the determination is made by combining the mean square displacement of interface region chain segments, hole connectivity, and ion directional transport parameters.